Christianity, Secular Society, and Politics from the Perspective of the Czech Thinker Tomáš Halík - Vašek, Martin (A journal of church and state, 2025)
Czech thinker, sociologist, and theologian Tomáš Halík is a leading Christian European intellectual. In his writings, he analyzes the place and role of Christianity in secular society and its relation to secular politics. He believes that Christianity belongs in politics and that its role is to be a counterplayer to political power and domination. He argues that the spiritual and political dimensions can never completely overlap. The political sphere tends towards self-sufficiency and immanence; as Bismarck said, politics is the art of the possible. In contrast, the spiritual dimension implies an openness to the "impossible," tending towards the new, the different, and the transcendent. Halík defines their relationship and reflects on their possibilities for cooperation. This study aims to clarify Halík’s view on the relationship between Christianity and secular society and politics. We discuss two issues—that of the religious-secular consensus and crisis and Halík’s appeal to engage in dialogue with the contemporary world to achieve a deeper understanding of it.